Surface Characteristics and Performance Optimization of W-Doped Vanadium Dioxide Thin Films - Chuen-Lin Tien; Chun-Yu Chiang; Jia-Kai Tien; Ching-Chiun Wang; Shih-Chin Lin (Surfaces)
This study explores the surface characteristics evaluation and performance optimization of tungsten (W)-doped vanadium dioxide (VO2) thin films. W-doped vanadium dioxide films were deposited on B270 glass substrates using an electron beam evaporation technique combined with the ion beam-assisted deposition (IAD) method. The Taguchi method was used to analyze the performance optimization of VO2 thin films, and L16 orthogonal array design and Minitab software were used for optimization calculations. The surface roughness, visible light transmittance, infrared transmittance, and residual stress of un-doped and tungsten-doped (3–5%) VO2 thin films are set as the quality performance indicators of thin films. The goal is to identify the key factors that affect the performance of VO2 thin films during deposition and optimize their process parameters. The experimental results showed that a VO2 thin film with 3% tungsten doping, an oxygen flow rate of 60 sccm, a heating temperature of 280 °C, and a film thickness of 60 nm exhibited the lowest surface roughness of 2.12 nm. A VO2 thin film with 5% tungsten doping, an oxygen flow rate of 0 sccm, a heating temperature of 280 °C, and a film thickness of 60 nm had the highest visible light transmittance at 64.33%. When the oxygen flow rate was 60 sccm, the heating temperature was 295 °C, the film thickness was 150 nm, and the tungsten doping was 5%, the VO2 thin film showed the lowest infrared transmittance of 31.34%. A thin film with 5% tungsten doping, an oxygen flow rate of 20 sccm, a heating temperature of 265 °C, and a film thickness of 120 nm exhibited the lowest residual stress of −0.195 GPa.